The impact of artificial intelligence on skills at work in Denmark - Holm, Jacob Rubæk; Lorenz, Edward (New technology, work, and employment, 2022)
Based on a unique dataset on the use of artificial intelligence (AI) among employees in Denmark, we investigate within‐job relationships between AI use and skill requirements. We show that the effects of AI are varied and depend on whether AI is used for providing orders to humans or providing information for further human handling and in which occupation it is used. AI may enhance or augment skills through, for example, the increased use of high‐performance work practices, or it may increase work pace constraints and reduce employee autonomy. The results imply that the diffusion of AI can increase inequalities in the labour market by augmenting skills used in high‐skill jobs, although having relatively more adverse impacts on other jobs. We use additive noise modelling to establish the likely direction of causality in our results and find that the direction of causality is from AI use to skill requirements.